Contribution of the Astronomy and the Mathematics to the Society in the Old Age - Rivel Pizarro, Eduardo Gabriel (2017)
In the old age, people had the curiosity and restlessness to observe the world around them; for example, the movement of the sun throughout the day, the movement of the celestial sphere and the direct movements of the stars and the moon in the night, also to the direct and retrograde movements of the planets. Thanks to observations of celestial bodies, they could predict dry and rainy seasons. To respond to these phenomena, were develop astronomy and mathematics, which had a positive impact on society of the time. Since remote times, mathematics had a preponderant role in the development of the human being, because of the basic need of counting days, moon periods, animals, crops, and other objects. Another significant contribution of mathematics is given by the need to measure either the length of a piece of wood, the distance of a road or the measurement of chronological time, in order to know more precisely, the best times to farming practices, establish meeting times or religious celebrations. Besides, mathematics played an essential role in the construction of roads, bridges, canals, buildings of houses, and temples around the ages.